Опыт практического внедрения беспроводных сенсорных сетей - Степанова, К. А. (ХНУРЕ, 2019)
Wireless Sensor Networks and the main features and difficulties in implementation have been considered. Some solutions of problems of introducing WSN using MeshLogic technologies have been offered